Karakterisasi Karbon Dari Tempurung Kemiri (Aleurites Moluccana (L) Willd) Dengan Alat XRD - Latupeirissa, Jola; Tanasale, Matheis F.J.D.P.; Dade, Kalam (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2016)
The research of carbon characterization from candlenut shells before and after activation has been done. Activated carbon were obtained through the heating process at 350 °C for 2 hours. The carbon charcoal were further cooled and sieved with a 100 mesh sieve. Then, calcinated at 450 °C and nitrogen (N2) were flowed for 2 hours and characterized by XRD for carbon before activation. Carbon was activated by using KOH solution with a concentration of 50% for 5 hours, then dried in an oven at 120 °C for 1 hour and characterized. XRD diffractogram of crystallization for carbon before activation produced three main peak were 2.93 Å, 3.25 Å, and 8.26 Å, and at 2Ө region of 30.47°, 27.40°, and 10.70°, respectively. XRD diffractogram of crystallization for activated carbon produced three main peak were 3.0195 Å, 3.3383 Å and 8.0955 Å, the 2Ө value which was shifted of 29.560°, 26.682°, and 10.920°. This shift indicates that the distance difference between charcoal crystal face caused by KOH activator. Weight acidity solids before and after activation was 27.370 x10-3 and 33.1245x10-3 mol.g-1, respectively.